The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/nar/gkv878
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-CAS9 D10A nickase target-specific fluorescent labeling of double strand DNA for whole genome mapping and structural variation analysis

Abstract: We have developed a new, sequence-specific DNA labeling strategy that will dramatically improve DNA mapping in complex and structurally variant genomic regions, as well as facilitate high-throughput automated whole-genome mapping. The method uses the Cas9 D10A protein, which contains a nuclease disabling mutation in one of the two nuclease domains of Cas9, to create a guide RNA-directed DNA nick in the context of an in vitro-assembled CRISPR-CAS9-DNA complex. Fluorescent nucleotides are then incorporated adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…To overcome this hurdle, McCaffrey et al (54) used a nicking enzyme based on the CRISPR/Cas9 system. While the wild-type Cas9 enzyme cuts both strands of the DNA molecule, the commercially available mutant enzyme Cas9 D10A, lacking one of the nuclease activity subunits, causes a nick in only one of the DNA strands, instead of breaking the molecule.…”
Section: Om In Microbiology: a New Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this hurdle, McCaffrey et al (54) used a nicking enzyme based on the CRISPR/Cas9 system. While the wild-type Cas9 enzyme cuts both strands of the DNA molecule, the commercially available mutant enzyme Cas9 D10A, lacking one of the nuclease activity subunits, causes a nick in only one of the DNA strands, instead of breaking the molecule.…”
Section: Om In Microbiology: a New Perspectivementioning
confidence: 99%
“…In fact, a recognition site of 20 base pairs means that a specific gene can be identified and targeted, even in the human genome. McCaffrey et al (54) used this principle to label several different genes that are not accessible with traditional nick labeling.…”
Section: Om In Microbiology: a New Perspectivementioning
confidence: 99%
“…23,24,134,135 We have already mentioned above that DNA linearization by equilibrium stretching inside a nanochannel is particularly suited for optical mapping of the genetic information along the DNA molecule. 24,[27][28][29]134,136 An optical map is obtained by fluorescently labeling specific parts (sequence motifs) along the DNA and can be used to identify structural variation in a genome, compare genomes, or detect pathogens. Stretching the DNA at equilibrium, however, has certain limitations.…”
Section: Physics Of Confined Dna: From the Odijk To The De Gennes Regimementioning
confidence: 99%
“…[22][23][24][25] To this end, the advancement of nanofabrication technologies 26 has provided unprecedented possibilities to study and manipulate DNA molecules in confined nanofluidic environments. Over the past decade, the use of nanofluidics for DNA manipulation has received enormous attention for applications such as genome mapping, [27][28][29] and DNA sequencing, 25,30,31 as well as for DNA sorting/separation, [32][33][34] and DNA transfer into live cells. 35 In this spirit, the present review article overviews the use of microfluidic and nanofluidic systems to visualize, study, and manipulate DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…McCaffrey et al . recently demonstrated that specific genes can be visualized in optical DNA maps using CRISPR/Cas917. The use of Cas9 for gene editing has exploded in the last years due to its versatility and specificity18.…”
mentioning
confidence: 99%